Exploring the geographical distribution of human cryptosporidiosis in Southern Ontario from 2011 to 2014. (13th March 2022) - Nwosu, Andrea; Berke, Olaf; Trotz‐Williams, Lise A.; Pearl, David L
Abstract: Cryptosporidium is a protozoan parasite of increasing global public health concern because of its ability to cause disease in both humans and animals through contaminated food and water supplies. In Canada, most human cryptosporidiosis cases are due to Cryptosporidium hominis ; however, the presence of zoonotic Cryptosporidium parvum has been observed. Since 2005, the incidence of cryptosporidiosis in Ontario has been consistently higher than the national average; however, it is not understood why, suggesting an incomplete understanding of the pathogen's ecology, epidemiology and transmission pathways. The goal of this study was to explore the spatial distribution of human cryptosporidiosis across the 29 Public Health Unit (PHU) areas of Southern Ontario from 2011 to 2014. Surveillance data on human cryptosporidiosis were obtained from Public Health Ontario. Choropleth and isopleth maps were used to display the distribution of incidence rates of human cryptosporidiosis. High‐rate clusters of human cryptosporidiosis were identified. Poisson and spatial Poisson regression models were used to determine the relationship between the incidence of human cryptosporidiosis, cattle density and the smoothed farm‐level prevalence of bovine cryptosporidiosis at the PHU level. The annual incidence of reported human cryptosporidiosis in Southern Ontario ranged from 1.62 (95% CI: 1.41–1.86) to 1.82 (95%CI: 1.60–2.06) cases per 100, 000 population, with an overall cumulative incidence of 6.91 (95%CI: 6.47–7.39) cases per 100, 000 for the 4‐year study period. High‐risk clusters of human cryptosporidiosis were identified in each year. The relative risk for the clusters ranged from 2.03 (95% CI: 1.63–2.55) to 6.87 (95% CI: 5.07–9.30). A relationship was found between the incidence of cryptosporidiosis and dairy cattle density. Based on this study, the Central West region would be an ideal ecological system to conduct further targeted surveillance to identify factors that may be contributing to the higher burden of cryptosporidiosis in the human and bovine populations in the region.